Exploring human computation via interactive online application - Lee, Ming Hua. (2010)
Training a computer vision algorithm to test whether an image contains a particular object, a dog for example, would involve presenting it with multiple images of a dog, each annotated with the precise location of the dog in the image. After processing enough images, the algorithm learns to find dogs in arbitrary images. A major problem with this approach, however, is the lack of training data which must be prepared by hand.